Violence against women before and during gestation: differences in prevalence rates and perpetrators - Marizélia Rodrigues Costa Ribeiro; Bianca Portela Teles Pessoa; Galvani Ascar Sauaia; Lilia Blima Schraiber; Rejane Christine de Sousa Queiroz; Rosângela Fernandes Lucena Batista; Joana Athayde da Silva Cruz; Antônio Augusto Moura da Silva
Abstract Objectives: to analyze differences in prevalence and perpetrators of violence against women before and during pregnancy. Methods: this is a cross-sectional study with a sample of 1,446 pregnant women interviewed in 2010 and 2011 in the São Luís municipality (Brazil). Thirteen questions measured psychological, physical and sexual violence in the 12 months before and during pregnancy. Psychological/physical/sexual violence was defined as any type of violence perpetrated against the interviewees. The perpetrators were categorized into intimate partner, other family members, community members, and multiple perpetrators. Differences between violence before and during pregnancy were analyzed by the chi-square test. Results: psychological/physical/sexual and psychological violence were more prevalent during pregnancy than before gestation (p<0.001). Insults, humiliation and intimidation (p<0.05) were more frequently reported during pregnancy. An intimate partner was the most frequent perpetrator. There were no differences in the percentage of moderate and severe forms of physical violence and sexual violence, recurrence of aggressions and perpetrators in both periods (p>0.05). Conclusions: gestation did not protect users of prenatal services in São Luís municipality from psychological, physical and sexual violence. Psychological/physical/sexual and psychological violence were more commonly practiced during pregnancy. The perpetrators of violence in the year before gestation continued to abuse the interviewees during pregnancy